Оцінка ризиків в інноваційних проектах методом достовірних еквівалентів - Шахов, Анатолій Валентинович; Пітерська, Варвара Михайлівна (НТУ "ХПІ", 2017)
У статті розглянуто поняття "ризик інноваційної діяльності", визначені причини появи ризику та методи усунення негативних проявів настання ситуацій ризику при інноваційному проектуванні. Визначені переваги і недоліки методу коригування норми дисконту, методу еквівалентних ануїтетів. Запропоновано методичний підхід при оцінці очікуваного ефекту інноваційного проекту на базі концепції інтервально-ймовірнісної невизначеності. Встановлено, що проаналізовані підходи можуть використовуватись для урахування ризику в інноваційних проектах.

The article describes the concept of "risk of innovation", identified the causes of the risk and the methods of eliminating of negative manifestations of the risk situations in innovative projects. The advantages and disadvantages of the method of correction of the discount rate and the method of equivalent annuities are considered. The methodical approach in assessing of the expected effect of the innovative project based on the concept of probability-interval uncertainty is proposed in the article. It was established that the analyzed approaches can be used for the accounting of the risk of innovative projects. Project manager makes his choice using any method of risk assessment individually, depending on the extent and characteristics of the project, the degree of novelty and scale introduction of innovative products, the number of participants and the level of requirements of foundation of project efficiency and other factors.
The risks’ assessment in innovative projects by the method of verified equivalents
Keywords: інноваційний проект; ризик; коригування норми дисконту; метод еквівалентних ануїтетів; innovation project; risk; discount rate correction; method of equivalent annuities